THE IMPORTANCE OF THE LINGUISTIC IMAGE OF THE WORLD TODAY - Rasulova Shahnoza Abduvasi qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article explores the concept of the linguistic image of the world and its growing relevance in modern society. The study emphasizes how language reflects a people’s worldview, cultural values, and historical experience. It highlights the role of the linguistic image of the world in intercultural communication, translation, language teaching, and the development of personal and national identity. The paper also discusses the cognitive and sociocultural functions of language as a tool for shaping human perception and interaction. Understanding the linguistic worldview is considered essential for fostering intercultural competence and ensuring effective communication in an increasingly globalized world.